Sick Economies : Drama, Mercantilism, and Disease in Shakespeare's England - Harris, Jonathan Gil (Book collections on Project MUSE., 2004)
The author integrates feminism, materialist criticism, and legal history to offer a look at how women's management of household goods became an important site of female struggle and resistance to England's patrilinear property regime.